PENGEMBANGAN MULTIMEDIA PEMBELAJARAN KOMPOSISI FOTO DIGITAL UNTUK MENINGKATKAN MINAT BELAJAR DAN HASIL BELAJAR - Handika Asep Kurniawan; Sunaryo Soenarto (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2022)
This study aims to develop multimedia learning digital photo composition subjects and determine the feasibility of the product is based on an expert assessment of materials and multimedia experts and to find out the effect of the use of multimedia learning for interest and learning outcomes students.This research is a development that adapts the ADDIE development model which comprises the step of analysis, design, development, implementation, and evaluation. Collecting data using questionnaire instrument learning interest and achievement test learners. The results showed that the eligibility rate products based on expert assessment of the material obtained a mean score of 3,75 (very decent) and multimedia experts obtained a mean score of 3,73 (very decent). The interest of learners who use multimedia learning digital photo composition subjects is higher than the interest of learners who use conventional multimedia learning with a significance value of 0,020. Then the learning outcomes of students who use multimedia learning digital photo composition subjects is higher than the learning outcomes who use conventional multimedia learning with a significance value of 0,000.